Analysis of Dust and NO2 Level in the Ambient Air and Sweeper's Respiratory Complaints in Purabaya Bus Station Sidoarjo - Amanda Fairuz Hikmiyah (JURNAL KESEHATAN LINGKUNGAN, 2018)
The air pollution can be impact for people's health who doing an activity in bus station. The study aims to analyze the levels of dust and NO2 in ambient air and the sweeper's respiratory complaints in Purabaya's Bus Station. This was a observational study with cross sectional design. The population are 34 subjects that was all sweepers in Purabaya's Bus Station using purposive sampling. Measurements of dust and NO2 level in the Bus Station's arrival and departure in the morning, afternoon, and evening. The variables in this study are the dust and NO2 level, individual charactheristics are age, length of work in a day, work period over the years, use Personal Protective Equipment (masks), and respiratory complaints such us cough, phelgm, shor t breath, and fast breath. Data were analyzed descriptively. The results indicate that dust and NO2 level was high and inappropriate the standard of Peraturan Gubernur Jawa Timur No. 10 tahun 2009 with an average concentrations are 2,946 mg/m3 and 165,93 Î¼g/m3. The respiratory complain such as cough (94,1%), phelgm (35,3%), short breath (35,3%), and fast breath (85,3%). It's recommended for sweepers to use mask while working, Manager of Bus Station should be monitors of ambient air quality and medical checking for sweeper's workers.